Coupling-to-diazonium role-convert strategy for 1, 3-dimethylbarbituric acid-based dyes and configurational confirmation via NMR/UV–vis spectra. (November 2022) - Ma, Hui; Zhao, Xiaolei; Yan, Suqiong; Wang, Hongjin; Yin, Gui; Huang, Wei
Abstract: 5-Amino-1, 3-dimethlybarbituric acid (5-amino-diMeBA), prepared form 1, 3-dimethlybarbituric acid (diMeBA) via the functional group transformation strategy, is first used as the diazonium component to produce heterocyclic dyes, in order to expand the existing research objects in this area. Role-convert synthesis has been successfully achieved from a general coupling component diMeBA to a corresponding diazonium unit 5-amnio-diMeBA, and three pyrazolone/pyridone coupled bi-heterocyclic dyes were yielded. There are multiple possible azo/hydrazone tautomers for them since three ortho -carbonyl groups could serve as the protonated sites for active protons. The configurational confirmation depends on the precise location of heterocyclic hydroxyl groups, which could be deduced by comparing the alterations of two characteristic methyl single peaks in diMeBA moiety in the 1 H NMR spectra before and after deprotonation. Our results reveal that three bi-heterocyclic dyes adopt the monohydrazone form in pyrazolone with 4-OH-diMeBA and the monohydrazone form in diMeBA with 6-OH-pyridone, respectively. Further UV–Vis spectra have been carried out to compare the delocalized π -conjugated system for them, together with three BA coupled heterocyclic dyes. In addition, solvatochromic and acid-base titration experiments were performed to verify the strength of intramolecular charge transfer within the whole molecules and the monohydrazone configuration for every bi-heterocyclic dye. Graphical abstract: Image 1 Highlights: 5-Amino-diMeBA was first used to synthesize three bi-heterocyclic dyes. The configuration for these hydrazone dyes is confirmed by NMR and UV–Vis. Solvatochromic and acid-base discoloration behaviors are studied.